Capacitive sensing for non-contact means of measurement - Tasnim, Rumana; Arshad, Atika; Khan, Sheroz; Ahmed, Musse Mohamud; Saquib, Nazmus (IIUM Press, 2011)
Capacitive sensors exhibit an electrical property called "capacitance" on the way to carry out the measurements. Capacitance is particularly defined for two conducting objects, across which the potential difference is connected. The plates are separated by an electrical insulating material named as dielectric that helps the parallel plates to uphold the stored electrical charges. Capacitive sensors are indeed capable of sensing a wide range of things-motion, chemical composition, presence of gaseous components, electric field straightforwardly. On the other hand, in an indirect manner, these sensors can also sense some variables which can be converted into motion or dielectric constant, such as pressure, acceleration, fluid level, and fluid composition